Exposure of Food Samples to Pulsed Microwave Radiation to Increase their Microbiological Safety and Shelf Life - Yu. V. Gulyaev; V. P. Meshchanov; B. M. Kats; N. A. Koplevatsky; A. A. Lopatin; K. A. Sayapin; V. A. Elkin; V. V. Komarov; V. B. Bayburin; A. P. Rytik (Проблемы особо опасных инфекций, 2022)
The aim of the study was to increase the efficiency of decontamination of biological material and media (by the example of food products) by pulsed (non-thermal) radio emission and asses the prospects of its application in medicine and biology.Materials and methods. To achieve the goal an experimental setup has been designed, manufactured and tested, which makes it possible to study the process of exposure of biological materials and media to pulsed (non-thermal) radio emission, in particular, by the example of food products. The basis of the method is optimum control of the electro-physical parameters of the irradiating radio signal, depending on the type of the irradiated object. We used pulsed magnetrons with operating frequency of (2.45±0.05) GHz, authorized for bio-medical research, generating pulsed radiation with an adjustable power within the range of 0.1...10 kW. The pulse repetition rate with a duty cycle of 500...10000 is 0.1...5 kHz. The setup has an operating chamber into which the test sample is placed, as well as additional elements of magnetron protection and measuring the parameters of the microwave power incident on biological object.Results and discussion. The setup has been successfully used to irradiate various food samples with pathogenic micro flora (Salmonella spp. etc.) with pulsed microwave radiation. In particular, as shown by the studies, the arithmetic mean number of pathogenic bacteria in the irradiated samples of minced meat decreased by 27.5 times after 28 days of storage as compared to the control group of non-irradiated samples. Preliminary conducted experiments in the field of investigating the effect of microwave radiation on the process of cell division and other aspects of electromagnetic field influence on pathological microorganisms confirm the prospects and the expediency of continuing the ongoing studies in medicine and biology.